Integrating Weekly Reflective Communication to Enhance Moral Ethics and Classroom Management Effectiveness (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The transition from elementary to junior high school is a crucial developmental stage characterized by emotional, social, and behavioral adjustments. Students often experience emotional instability, declining ethical awareness, and weakened communication skills, which negatively affect classroom dynamics. This study aims to examine the effectiveness of integrating weekly reflections with structured teacher–student communication as a strategy to enhance moral and ethical character while supporting effective classroom management. Using a mixed-methods design, data were collected through classroom observations, students’ weekly written reflections, and online questionnaires. Qualitative data were analyzed thematically to identify changes in behavior and attitudes, while quantitative data were analyzed descriptively to assess improvement patterns. The results indicate that consistent engagement in weekly reflections enhances students’ self-awareness, empathy, critical thinking, and self-regulation. Reflective communication between teachers and students also fosters mutual understanding, respect, and a harmonious classroom climate. This study confirms that integrating reflection and communication is effective in strengthening moral and ethical development and supports positive classroom management for students transitioning to junior high school.